METHODOLOGICAL RECOMMENDATIONS FOR PARENTS ON THE PREVENTION AND CORRECTION OF FACTORS CONTRIBUTING TO SPEECH DISORDERS IN PRESCHOOL CHILDREN - Ibrohimjonova Jannatxon Ibrohimjon qizi (Web of Journals Publishing, 2025)
This article discusses methodological recommendations for parents on the prevention and correction of factors that cause speech disorders in preschool children, as well as the use of fairy tale therapy to eliminate speech disorders in children.
Keywords: Correctional work, speech impairment, development, communication, fairy tale therapy, cooperation, factor, cognitive activity.